The Effects of Conditioning Training on Body Build, Aerobic and Anaerobic Performance in Elite Mixed Martial Arts Athletes - Tota, Łukasz (J Hum Kinet, 2019)
The aim of the study was: 1. to evaluate the effects of conditioning training on body build and physical fitness in elite mixed martial athletes, 2. to investigate the training load structure and assess body build as well as the physiological profile of mixed martial arts athletes. Fifteen MMA male athletes (body mass: 79.8 ± 3.9 kg; body height: 178.7 ± 7.9 cm; body fat: 13.4 ± 1.6%) were involved in the study. The average training experience of athletes equalled 11 ± 1.1 years. Body composition, upper limb peak anaerobic power and aerobic performance were assessed before and after the preparatory phase. During each evaluation, athletes underwent two stress tests: the Wingate test for the upper limbs (upper limb anaerobic peak power measurement) and the graded exercise test until volitional exhaustion (maximal oxygen uptake measurement and second ventilatory threshold determination). Training means were investigated for the workload type, intensity and exercise metabolism. In the follow-up, body fat mass decreased, while anaerobic peak power and aerobic performance improved. Improvement in the time to obtain and maintain peak power in the upper limbs was noted. Training periodization resulted in advantageous body composition changes and improved physical fitness of the MMA athletes.